Stigma and Its Impact on the Psychological Well-Being of LGBT Individuals in the Context of Community Life - Dhiyaa Azmi (Jurnal Psikologi Perseptual, 2025)
Social stigma against LGBT individuals in Indonesia remains a serious issue that can affect their psychological well-being. In a society that often lacks acceptance of sexual diversity, conservative cultural and religious norms reinforce the stereotypes, prejudices, and discrimination they experience. A number of studies have highlighted the issue of stigma, but research focusing on the experiences of young LGBT people in the emerging adulthood phase (20–23 years) is still limited, even though this period is an important phase of identity formation that is vulnerable to social pressure. Therefore, this study aims to explore the experiences of stigma, the influence of cultural and religious values, and the coping strategies used by LGBT individuals in facing social pressure. This study uses a qualitative approach with a phenomenological design. Three participants, aged 20–23 years, living in urban and suburban areas of Indonesia, were interviewed online via the Zoom platform twice each. The data were analyzed using thematic analysis to find patterns of meaning in the participants' narratives. The results of the study identified the main themes of experiences of stigma (stereotypes, prejudice, discrimination), the impact on psychological well-being, the influence of culture and religion, social support, and coping strategies such as self-acceptance. These findings emphasize the importance of interventions based on social support, inclusive education, and community advocacy to reduce stigma and improve the well-being of LGBT people in Indonesia.